A model to predict upstaging to invasive carcinoma in patients preoperatively diagnosed with ductal carcinoma in situ of the breast. Issue 5 (8th September 2015) - Kondo, Takafumi; Hayashi, Naoki; Ohde, Sachiko; Suzuki, Koyu; Yoshida, Atsushi; Yagata, Hiroshi; Niikura, Naoki; Iwamoto, Takayuki; Kida, Kumiko; Murai, Michiko; Takahashi, Yuko; Tsunoda, Hiroko; et al.
<x xml:space="preserve">Abstract</x> Background The aims of this study were to determine clinicopathological factors associated with postoperative upstaging to invasive carcinoma in patients preoperatively diagnosed with ductal carcinoma in situ (DCIS) and to develop a model to predict the risk of upstaging. Methods Pre‐ and post‐operative pathological diagnoses and radiological findings were assessed for 1, 187 consecutive patients. Results Of the patients, 306 (25.8%) were upstaged on the surgical specimen. In multivariate analysis, the following four factors were significantly associated with upstaging: 1) the presence of sclerosing adenosis on the preoperative biopsy specimen (odds ratio [OR] 0.46, P = 0.013); 2) pleomorphic calcifications on the mammogram (OR 1.68, P = 0.009); 3) a mass suspicious for invasive carcinoma on ultrasonography and/or MRI (OR 2.13, P < 0.001); 4) tumor size ≥2 cm on ultrasonography (OR 1.80, P = 0.032). HER2‐positive (OR 1.54, P = 0.062) and comedo necrosis (OR 1.42, P = 0.056) demonstrated a trend towards significance. A prediction model incorporating these variables demonstrated that the risk of upstaging was 5.1% with score 0–2 and was 58.1% with score 10. Conclusions The prediction model incorporating clinicopathological features may be used to guide the selection of patients with DCIS for sentinel lymph node biopsy. J. Surg. Oncol. 2015; 112:476–480. © 2015 Wiley Periodicals, Inc.